Leveraging SMEs’ Competitiveness Through Innovation and Standardization: Case Study of SMEs In Medical Device - Hardiyati, Ria; Purwaningsih, Indah (STI Policy and Management Journal, 2023)
Indonesia's medical devices industry indicates substantial growth recently. However, domestic products are less competitive than imported products. This study tries to fill the gap by presenting a more robust analysis on the collaborative innovation process of new medical devices to support SMEs’ competitiveness through innovation and standardization. This study employed qualitative case study approach by using holistic multiple case design, namely HFNC and Dharcov-23S GLP innovation process. We have discovered the activities in the standardization process for each stage of the innovation process and the specific type of standards that SMEs should fulfill. We also capture multi-stakeholder cooperation in supporting SMEs in each activity. As result, the role of multi-stakeholder collaboration is highlighted in supporting SMEs along the innovation and standardization process to gain market competitiveness. Actors involved in each innovation process activity have disparate backgrounds, capabilities, and knowledge, such as PRI, industry, government (Public testing laboratory, National Public Procurement Agency, MoH), medical experts, hospitals, and users.